Dynamic Performance Analysis of High-Frequency Signal Injection Based Sensorless Methods for Interior Permanent Magnet Synchronous Motors - Ahmadreza Alaei; Dong Hee Lee; Jin woo Ahn; Sayed Morteza Saghaeian Nejad (AUT Journal of Electrical Engineering, 2019)
This paper focuses on three commonly used sensorless methods based on high-frequency signal injection; namely, the rotating sinusoidal injection in the stationary reference frame, the pulsating sinusoidal injection in the estimated synchronous reference frame, and the pulsating square wave injection in the estimated synchronous reference frame. Although these methods have found applications in interior permanent magnet synchronous motor (IPMSM) sensorless drives. Some efforts have been performed to compare such high frequency signal injection based methods from viewpoint of some parameters such as injection frequency, voltage magnitude and so on. However, evaluation of their dynamic seems to await further investigation and evaluation. Hence, some of motor parameters such as pole number, machine saliency ratio, that affect the performance of the saliency based sensorless methods are evaluated in this paper. Moreover, some such other parameters in driver circuit such as current measurement noise, effect of time delay on demodulation, and load disturbance effect are also explored. The maximum torque per ampere (MTPA) strategy is employed to improve motor driven torque and overcome the load torque by using of the reluctance torque component. Finally, simulation and experimental results are used to investigate the effects of the above parameters on the performance of high frequency signal injection based sensorless methods.